2009
DOI: 10.1128/jvi.02195-08
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr Virus (EBV) Deubiquitinating Enzyme BPLF1 Reduces EBV Ribonucleotide Reductase Activity

Abstract: A newly discovered virally encoded deubiquitinating enzyme (DUB) is strictly conserved across the Herpesviridae. Epstein-Barr virus (EBV) BPLF1 encodes a tegument protein (3,149 amino acids) that exhibits deubiquitinating (DUB) activity that is lost upon mutation of the active-site cysteine. However, targets for the herpesviral DUBs have remained elusive. To investigate a predicted interaction between EBV BPLF1 and EBV ribonucleotide reductase (RR), a functional clone of the first 246 N-terminal amino acids of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 47 publications
1
77
0
Order By: Relevance
“…Polymorphisms in the genes encoding tegument and early lytic proteins and glycoproteins have been identified here. BPLF1 is one of the few tegument proteins whose function has been relatively well investigated (41). We identified two nonsynonymous mutations in the N-terminal region of the protein that exhibits deubiquitinating activity.…”
Section: Discussionmentioning
confidence: 98%
“…Polymorphisms in the genes encoding tegument and early lytic proteins and glycoproteins have been identified here. BPLF1 is one of the few tegument proteins whose function has been relatively well investigated (41). We identified two nonsynonymous mutations in the N-terminal region of the protein that exhibits deubiquitinating activity.…”
Section: Discussionmentioning
confidence: 98%
“…The calcium phosphate technique [7] was used to transfect 10 lg per well and 50 lg per dish of the plasmids pAdCMV5 (empty), pAdCMV5-R1 (HSV-2 R1); pLBPF1-GST (GST), pLBPF1-GST-R1 (GST-HSV-1 R1) (kindly provided by A. Pearson); pcDNA3 (empty), pcDNA3-HA-EBV R1 (HA-EBV R1) [29]; pEGFP C1 (GFP) and plasmids encoding for caspase-8 GFP (casp-8 GFP), caspase-8 C360S GFP (casp-8 C360S GFP), caspase-8 DED-AB (1-209) GFP (casp-8 DED-AB GFP), caspase-8 CD (210-479) GFP (casp-8 CD GFP) and FADD YFP [30]. Immunofluorescence was performed on cells fixed with paraformaldehyde as previously described [31].…”
Section: Transfection and Immunofluorescencementioning
confidence: 99%
“…Recently, a number of studies have shown that herpesviridae have large tegument proteins with a DUB domain embedded at their N terminus, such as herpes simplex virus 1 (HSV-1) UL36 USP , mouse cytomegalovirus (MCMV) M48, human cytomegalovirus (HCMV) UL48, EBV BPLF1, and KSHV and MHV68 ORF64 (11,14,25,26,31). These viral tegument DUBs can cleave either Lys48-or Lys63-linked polyubiquitin chains in in vitro deubiquitination assays (11,16,26,33). Since ubiquitination plays a critical role in RIG-I signaling (10), we tested whether KSHV ORF64 inhibits RIG-I function.…”
mentioning
confidence: 99%